A Case of Multiple Endocrine Neoplasia Type 1: A Rare Clinical Entity - Chowdhury, Md Atiquel Islam (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background and purpose: Multiple endocrine neoplasia is a rare clinical entity which comprises a group of patients who has primary hyperparathyroidism. Case report: A 44-year-old male came with the complaints of generalized aches and pains in different parts of body with predominant involvement of small joints of hand associated with fatigue specially more pronounced in the early morning and usually it was relieved by taking repeated sugar containing drinks leading to weight gain. He has features suggestive of acromegaly as evidenced by prognathism, prominent heal pad thickness, and coarse spade like fingers. He has hyperparathyroidism as evidenced by raised serum calcium and parathormone level and acromegaly as evidenced by raised serum growth hormone and insulin-like growth factor-1 level. His PET-CT whole body showed pituitary macroadenoma, tumour involving the tail of pancreas (insulinoma). So these multiple endocrine tumour in a single patient with a positive family history of primary hyperparathyroidism strongly suggests a genetic predisposition of the condition which convincingly can be attributed to multiple endocrine neoplasia type 1. MEN 2A and 2B and Familial Medullary Thyroid Cancer (FMTC) is being excluded by absence of medullary thyroid Cancer as evidenced by absence of thyroid mass on PET-CT. Conclusion: Multiple endocrine neoplasia, although a rare clinical entity, should be kept in mind in cases of hypercalacemia due to primary hyper parathyroidism. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.45 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 66-69